2002
DOI: 10.1063/1.1467328
|View full text |Cite
|
Sign up to set email alerts
|

Resonances in the O(3P)+HCl reaction due to van der Waals minima

Abstract: Quantum scattering calculations of the O ( 1 D)+ HCl reaction using a new ab initio potential and extensions of Jshifting J.Quantum reaction dynamics of O ( 3 P) +HCl on a new ab initio potential energy surface Dynamics of the O ( 3 P)+ HCl reaction on the 3 A ″ electronic state: A new ab initio potential energy surface, quasi-classical trajectory study, and comparison to experimentWe present extensive exact quantum calculations of the cumulative reaction probability ͑CRP͒ for the O( 3 P)ϩHCl→OHϩCl reaction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 26 publications
0
57
0
2
Order By: Relevance
“…[1][2][3][4][5][6] The complex Cl( 2 P)-HF that occurs in the entrance channel of the reaction Cl + HF f F + HCl was recently prepared in helium nanodroplets and studied by high-resolution infrared laser spectroscopy. 7 The preceding paper 8 describes the ab initio calculation and analytic representation of the full 3 × 3 matrix of diabatic potentials required to compute the bound states of this complex with the inclusion of the nonadiabatic Renner-Teller coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The complex Cl( 2 P)-HF that occurs in the entrance channel of the reaction Cl + HF f F + HCl was recently prepared in helium nanodroplets and studied by high-resolution infrared laser spectroscopy. 7 The preceding paper 8 describes the ab initio calculation and analytic representation of the full 3 × 3 matrix of diabatic potentials required to compute the bound states of this complex with the inclusion of the nonadiabatic Renner-Teller coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic Br has a 2 P ground state with the configuration ͓Ar͔(3d) 10 (4s) . Since the z axis is the interatomic axis, the first two of these are degenerate and form a ⌸ state with potential curve V ⌸ (R), while the third forms a ⌺ state with potential curve V ⌺ (R).…”
Section: ͑1͒mentioning
confidence: 99%
“…For example, Maierle et al 6 and Dobbyn et al 7 have developed full reactive potentials for Cl-HCl that incorporate the Dubernet-Hutson potential at long range, and these have been used to show that the long-range well has important effects on the positions of reactive scattering resonances and to calculate thermal rate coefficients. 8,9 Xie et al 10 have shown that long-range forces are responsible for prominent resonances in the O ( 3 P)ϩHCl reaction, while Skouteris et al 11 have shown that such forces play a decisive role in determining the product isotope ratio in the ClϩHD reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently these reactive resonances have been observed in experimental studies of these reactions, H + D2 + HD +D [6], H + HD + D + H2 [7] and F + HD -+ HF + D [8]. There The second is the result of quasibound states localized in the van der Waals well of either the entrance or exit channel, such as the resonances in 0 + HC1 reaction [9]. The third type occurs when the reacting system has a chemically bound state with a barrier to the asymp- The first quantum dynamics study of the cumulative reaction probabilities and chemical reaction rates of the N+N2 exchange reaction, as well as the first ab initio potentia1 energy surface(PES) for the N3 system, have been reported by this group [ll].…”
mentioning
confidence: 99%
“…!PFi(E, R) is the scattering wave funct ion. complex Hamiltonian matrix using the L2 method with an absorbing potential in the reactant channel [9]. The stationary eigenvalues are identified as be the quasibound states, and the real and imaginary parts of these eigenvalues give the resonance energies and widths.…”
mentioning
confidence: 99%